IDENTIFICATION AND EXAMINATION OF CERTAIN CYTOGENETIC CHARACTERISTICS OF SOME AUTOCHTHONOUS VARIETIES OF GRAPEVINE IN REPUBLIC OF NORTH MACEDONIA - Korunoska Biljana; Pešić Vladan; Bunjac Nenad (Journal Genetika, Belgrade, 2023)
Abstract In R.N. Macedonia has a large number of autochthonous or domestic varieties (cultivars) of grapevine that are grown as individual vines or in small, limited plantations. Until the beginning of the 20th century and before the phylloxera attack in our country, native varieties were much more represented. Autochthonous varieties existed and were cultivated for a long time in several vineyards and were characterized by stable and significant properties. These varieties are adapted to the environmental conditions where they are grown and are carriers of stable genes that can be used in further selection and hybridization to obtain new grape varieties. Therefore, it is very important for a country (region) to have autochthonous varieties in its assortment.In this paper, we considered four autochthonous grape varieties - two table varieties (Konchanka and white winter) and two wine varieties (Ohrid white, Ohrid black). We tried, according to the ampelographic description and certain characteristics of the reproductive system, to determine their origin. According to the phenotypic characteristics that refer to the centers of origin of the varieties, the studied varieties - Konchanka and White winter belong to the Eastern varieties convarietas orientalis, subconvarietas antasiatica, and the studied varieties Ohrid white and Ohrid black variety belong to the Black Sea - Balkan varieties convarietas. pontica, subconvarietas balcanica. Among the examined varieties, the properties from the second group of descriptors are described in detail according to the proposals of O.I.V. According to some codes (characteristics) there is a big difference between varieties. Also, for a more detailed differentiation of the varieties, cytological properties were examined - pollen germination and vitality, number of chromosomes in mitosis and meiosis, ploidy level, percentage of fertilization (fecundation), self-fertilization (autogamy) and cross-fertilization (xenogamy). The statistical processing of the ampelography data is according to a cluster program (SPSS) that works on the binary similarity or dissimilarity as measures used to group the data and further form a clear dendogram display.
IDENTIFIKACIJA I ISPITIVANJE POJEDINIH CITOGENETSKIH KARAKTERISTIKA NEKIH AUTOHTONIH SORTI VINOVE LOZE U REPUBLICI SEVERNOJ MAKEDONIJI
Keywords: ampelographical description, autochthonous varieties, chromosomes, cytological properties